2004
DOI: 10.1162/003465304323031139
|View full text |Cite
|
Sign up to set email alerts
|

Returns to Birthweight

Abstract: We use data on monozygotic twins to obtain improved estimates of the effect of intrauterine nutrient intake on adult health and earnings and thus to evaluate the efficacy of programs aimed at increasing birthweight. We use the results to evaluate the bias in cross-sectional estimates and to assess the proposition that health conditions play a major role in determining the world distribution of income. We show that there is considerable variation in the incidence of low birthweight across countries, and our est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
523
4
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 760 publications
(549 citation statements)
references
References 27 publications
20
523
4
2
Order By: Relevance
“…Of course, in doing that, a note of caution is warranted. Although it is true that the twin estimates control for unobservable factors capturing the in utero environment (Behrman and Rosenzweig, 2004), they are based on a selected sample: the average birth weight and the proportion of LBW is much lower for twins.…”
Section: Long-lasting E¤ects: a Lower Bound Estimatementioning
confidence: 99%
“…Of course, in doing that, a note of caution is warranted. Although it is true that the twin estimates control for unobservable factors capturing the in utero environment (Behrman and Rosenzweig, 2004), they are based on a selected sample: the average birth weight and the proportion of LBW is much lower for twins.…”
Section: Long-lasting E¤ects: a Lower Bound Estimatementioning
confidence: 99%
“…In particular, a number of studies in the economics literature have shown the importance of birth weight for outcomes such as education, earnings, and cognition (e.g., Currie and Hyson 1999;Behrman and Rosenzweig 2004; 1 The authors thank Janet Currie and seminar participants at Lund University, at the Health and Human Capital Workshop in Mannheim, at the RGS Doctoral Conference in Duisburg, at the RES Conference in Cambridge, at the ASHE Conference in Minneapolis, at the EEA Conference in Gothenburg and at the EALE Conference in Turin for useful comments and suggestions. We also thank Ingvar Ahlstrand and Björn Bäckstand at the National Service Administration for providing information on the enlistment data and procedure.…”
Section: Introductionmentioning
confidence: 99%
“…MZ twins hold constant genetic differences that may influence both birth weight and the outcome of interest. Behrman and Rosenzweig (2004) established that birth weight within identical twin pairs is unrelated to other observed measures in their data and illustrated a substantial distribution of birth-weight differences between identical twins. We then ask whether the treatment effect of low birth weight varies across twin pairs that are divergent on measured alleles.…”
Section: Methodsmentioning
confidence: 90%
“…Caloric deprivation, in turn, affects the fetus, with lasting impacts. One estimate asserts that in the developing world, birth weight (i.e., fetal nutrition) influences gross domestic product (Behrman and Rosenzweig 2004). Of course, in the population at large, there are multiple causes of low birth weight.…”
Section: Methodsmentioning
confidence: 99%